A Comparison of Double Poling Physiology and Kinematics Between Long-Distance and All-Round Cross-Country Skiers - Torvik, Per-Øyvind; Sandbakk, Øyvind; van den Tillaar, Roland; Talsnes, Rune Kjøsen; Danielsen, Jørgen (Frontiers in sports and active living, 2022)
The objective of this study was to compare physiological and kinematic responses to double poling (DP) between long-distance (LDS) and all-round (ARS) cross-country skiers. A number of five world-class LDS (28.8 ± 5.1 years, maximal oxygen uptake (VO ): 70.4 ± 2.9 ml·kg ·min ) and seven ARS (22.3 ± 2.8 years, VO : 69.1 ± 4.2 ml·kg ·min ) athletes having similar training volumes and VO performed three identical tests; (1) submaximal and incremental tests to exhaustion while treadmill DP to determine gross efficiency (GE), peak oxygen uptake (DP-VO ), and peak speed; (2) submaximal and incremental running tests to exhaustion to determine GE, VO (RUN-VO ), and peak speed; and (3) an upper-body pull-down exercise to determine one repetition maximum (1RM) and peak power. Physiological responses were determined during both DP and running, together with the assessments of kinematic responses and electromyography (EMG) of selected muscles during DP. Compared to ARS, LDS reached higher peak speed (22.1 ± 1.0 vs. 20.7 ± 0.9 km·h , = 0.030), DP-VO (68.3 ± 2.1 vs. 65.1 ± 2.7 ml·kg ·min , = 0.050), and DP-VO /RUN-VO ratio (97 vs. 94%, = 0.075) during incremental DP to exhaustion, as well as higher GE (17.2 vs. 15.9%, = 0.029) during submaximal DP. There were no significant differences in cycle length or cycle rate between the groups during submaximal DP, although LDS displayed longer relative poling times (~2.4% points) at most speeds compared to ARS ( = 0.015). However, group × speed interaction effects ( < 0.05) were found for pole angle and vertical fluctuation of body center of mass, with LDS maintaining a more upright body position and more vertical pole angles at touchdown and lift-off at faster speeds. ARS displayed slightly higher normalized EMG amplitude than LDS in the muscles rectus abdominis ( = 0.074) and biceps femoris ( = 0.027). LDS performed slightly better on 1RM upper-body strength (122 vs. 114 kg, = 0.198), with no group differences in power in the pull-down exercise. The combination of better DP-specific aerobic energy delivery capacity, efficiency, and technical solutions seems to contribute to the superior DP performance found among specialized LDS in comparison with ARS.